Impact of Nationality and Educational Diversity on CSR Performance: The Moderating Role of CEO Overconfidence - Khairunnisa Khairunnisa; Sylvia Veronica Siregar (AIBPM Publisher, 2022)
The sustainability report has attracted the attention of various business organizations and has become an essential issue in corporate sustainability and already required to report based on POJK No 16/SEOJK.04/2021. This study examines the relationship between board diversity and corporate social responsibility (CSR). This study used the nationality and educational dimension of board diversity by applying Blau's index. The upper echelons, stakeholders, and resource dependence theory are used to evaluate the hypothesized relationship through an empirical investigation of Indonesia's listed companies from 2011 to 2021. Indonesia used a two-tier corporate governance system, and this paper has been hypothesized by the board of directors (BOD) ) and board of commissioners (BOC) systems. BOD and CSR used CEO overconfidence as a moderating variable because there was a direct relationship between BOD and CEO overconfidence. Control variables for this paper are (1) profitability, (2) leverage, (3) size, (4) board meetings, and (5) board size. The results showed that the Board of Directors (BOD) positively related to CSR. CEO Overconfidence also strengthens the relationship between the Board of Directors (BOD) Educational and CSR in the company.